2017
DOI: 10.1002/2017jg003826
|View full text |Cite
|
Sign up to set email alerts
|

Strong Gradients in Forest Sensitivity to Climate Change Revealed by Dynamics of Forest Fire Cycles in the Post Little Ice Age Era

Abstract: The length of the fire cycle is a critical factor affecting the vegetation cover in boreal and temperate regions. However, its responses to climate change remain poorly understood. We reanalyzed data from earlier studies of forest age structures at the landscape level, in order to map the evolution of regional fire cycles across Eastern North American boreal and temperate forests, following the termination of the Little Ice Age (LIA). We demonstrated a well‐defined spatial pattern of post‐LIA changes in the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…Following the 1890 0 s fires, HBC archival records revealed that fire activity declined into the 1900s (Fritz et al 1993), which is consistent with information from the multi-proxy fire history. The advent of the 20th century marks a sharp transition toward a reduction of widespread synchronous fire years among large regions, likely brought by increases in the amount of precipitation associated with a strengthening of the Continental Polar Trough and jet stream displacement (St. George 2007, Drobyshev et al 2017). The 1988 fire, man-made, was the last large fire having hit the study area.…”
Section: Climate and Fire Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…Following the 1890 0 s fires, HBC archival records revealed that fire activity declined into the 1900s (Fritz et al 1993), which is consistent with information from the multi-proxy fire history. The advent of the 20th century marks a sharp transition toward a reduction of widespread synchronous fire years among large regions, likely brought by increases in the amount of precipitation associated with a strengthening of the Continental Polar Trough and jet stream displacement (St. George 2007, Drobyshev et al 2017). The 1988 fire, man-made, was the last large fire having hit the study area.…”
Section: Climate and Fire Activitymentioning
confidence: 99%
“…, Drobyshev et al. ). Albeit climate is likely to be a primary driver of this decreasing fire activity during recent decades, other confounding effects from European settlement and passive and active fire suppression may also have played a key role in driving these trends (Lefort et al.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Indeed, a vast majority of the studies looking at climate-fire interactions in the boreal zone has been done in Fennoscandia ( Aakala et al 2018) and references inside), a region experiencing a much stronger influence of North Atlantic climate as compared to more easterly located sections of EBZ. The increase in climate continentality towards easterly section of EBZ is be of particular interest in understanding the response of forest fire regimes to climate variability as previous studies have pointed to higher sensitivity of more continental boreal forests to historic climate changes Drobyshev et al 2017).…”
Section: Introductionmentioning
confidence: 99%